STUDY AND POTENTIAL UTILIZATION OF SOLAR POWER PLANT AS A SOURCE OF ENERGY AT UNIVERSITY OF PEMBANGUNAN PANCA BUDI - Anisah, Siti; Tarigan, Amani Darma; Wardhani, Dwi Putri (Proceeding International Conference of Science Technology and Social Humanities, 2022)
Indonesia is located on the equator so it has two seasons, namely the rainy season and the dry season. Indonesia has the potential to utilize this energy to be converted into electrical energy. PLTS (Solar Power Plant) is a power plant that utilizes solar energy using the main tool, namely solar modules. Solar modules are devices that can convert solar energy into electrical energy, this process is called the photovoltaic effect. PLTS can be installed in buildings, apartments, houses, factories and vacant land. The purpose of installing PLTS is to reduce electricity consumption from the network to reduce monthly electricity bills. PLTS On-Grid is a PLTS configuration system that is connected to the network with the KWh EXIM tool which functions to send excess electricity generated by PLTS to the network. In general, On-Grid PLTS is installed on the roof of the house. This aims to save land and no objects that will block the solar modules. There are many requirements for installing PLTS on the roof of a house such as the location of the area, the direction of the roof of the house, the roof area where the solar module will be installed, and the tilt of the solar module. These conditions serve to optimize the performance of solar modules. Panca Budi Development University is one of the universities that implements the use of green energy, various efforts have been made to realize the green energy program, one of the innovations that needs to be done is the use of PLTS as a substitute for generating sources. This rationale is supported by government policies regarding the utilization of environmentally friendly energy so that it becomes one of themThis research indicator is very important to provide/offer solutions to the problems experienced by the community. Research with a basic research method approach is carried out through an approach of observation, analysis, of existing conditions regarding data on wind conditions, weather, sunlight, and analysis of the required power requirements to facilitate energy needs in Building I, Panca Budi Development University.